KEMAMPUAN MENGAJAR MAHASISWA PRODI PENDIDIKAN TEKNOLOGI AGROINDUSTRI SECARA DARING DAN LURING PADA PELAKSANAAN PPL SATUAN PENDIDIKAN TAHUN AJARAN 2020/2021 - Deriztian, Salsabila Zaha (2020)
The activities of teaching internship program (Program Pengenalan Satuan Pendidikan) or PPL-SP are usually carried out face-to-face, but the pandemic that has occurred in Indonesia since the beginning of March 2020 has caused all schools in Indonesia to carry out teaching and learning activities remotely, including vocational schools which are used as places for PPL-SP, so that students who practice PPL-SP cannot continue their teaching and learning activities face-to-face or offline. Until now, the teaching ability of students of the Agroindustrial Technology Education Study Program in implementing PPL-SP online and offline is unknown. Therefore, the purpose of this research is to provide an overview of the teaching ability of students practicing PPL-SP in the Agro-Industrial Technology Education Study Program online and offline. The teaching ability of PPL-SP students consists of several aspects, namely 1) preliminary aspects; 2) Aspects of core activities; 3) Aspects of implementing educational learning strategies; 4) aspects of the use of learning resources / media in learning; and 5) Concluding aspects. The method used in this research is descriptive quantitative method. The research data collection was carried out through a questionnaire in the form of a Google Form which was assessed by respondents of Tutor Teachers and Students who were spread across two schools where the PPL-SP FPTK UPI Agroindustrial Technology Education Study Program was implemented in the Odd Semester of the 2020/2021 Academic Year which had been determined as a research sample, namely SMK Negeri 1 Sukaluyu and SMK Negeri 2 Cilaku. The results showed that the assessment given by the Tutor Teachers and Students on the teaching ability of PPL-SP Students as a whole was based on the aspects of existing teaching abilities, PPL- SP students were able to carry out learning activities online and offline in very good categories.